Penggunaan Campur Kode oleh Guru dan Siswa dalam Kegiatan Pembelajaran Bahasa Indonesia Kelas X di SMA Negeri 1 Barumun Tengah - Bitasbiyah Hasanah; Nirmawan (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aims to describe the form, factors and implementation of speech code mixing education for teachers and students in Indonesian language learning activities for class X at SMA Negeri 1 Barumun Tengah. This study uses qualitative research methods. The source of the data in this study was obtained from an area with the majority of the Mandailing ethnicity, making it easier for someone to communicate in their mother tongue (Mandailing). The data collection of this research used the note-taking technique and documented it in the form of a dialogue. In this study there was the use of internal code mixing using the Indonesian-Mandailing language. This is the factor why students at SMA Barumun are mastering two languages ??or also known as bilingualism. Based on the results of research and discussion, there are things that need to be conveyed in this study. First, the form of code-mixing in this study is a mixture of Indonesian and Mandailing languages. As for the use of code-mixing in the data, there are several forms including Indonesian-Mandailing language.